Protein hydrolysates as functional food ingredients: A bibliometric analysis from inception to 2023 - Ketemepi, Hilary Kwesi; Siti Faridah, Mohd Amin; Norliza, Julmohammad; Nazikussabah, Zaharudin; Nor Qhairul Izzreen, Mohd Noor (Elsevier, 2025)
Protein hydrolysates contain a mixture of amino acids, oligopeptides, and polypeptides with improved functionalities, making them valuable functional ingredients for diverse applications. Recently, hydrolysates have garnered considerable attention because of their usefulness in numerous industries. This bibliometric analysis evaluated research development in protein hydrolysate-related studies from 1933 to 2023 using the Scopus database to enhance knowledge and identify research trends. A three-phase methodology—comprising planning, data collection, and analysis—was employed. After applying inclusion and exclusion criteria, a total of 11,578 publications were analyzed using bibliometric tools such as Biblioshiny (R Studio), VOSviewer, and CiteSpace. The most prolific author was Soottawat Benjakul from Prince of Songkla University, Thailand, with 63 publications. The South China University of Technology led institutional contributions with 430 articles. The strategic emphasis on food security both nationally and globally by the Chinese government might have contributed to China’s leading position as the top country contributing significantly to protein hydrolysate-related research, and also reflected by the high output of top contributing institutions from China. A notable shift is observed in basic hydrolysis and nutritional evaluations toward more integrated, health-focused and sustainability-driven research themes. Future studies are expected to explore underutilized protein sources, improve bioactive peptide identification through multi-omics technologies and machine learning, and strengthen clinical validation for therapeutic applications. The insights gained on this subject can guide future research and policy development.